2007
DOI: 10.1016/j.taap.2007.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of CYP 2E1 enzyme in ovotoxicity caused by 4-vinylcyclohexene and its metabolites

Abstract: 4-Vinylcyclohexene (VCH) is bioactivated by hepatic CYP 2A and 2B to a monoepoxide (VCM) and subsequently to an ovotoxic diepoxide metabolite (VCD). Studies suggest that the ovary can directly bioactivate VCH via CYP 2E1. The current study was designed to evaluate the role of ovarian CYP 2E1 in VCM-induced ovotoxicity. Postnatal day 4 B6C3F(1) and CYP 2E1 wild-type (+/+) and null (-/-) mouse ovaries were cultured (15 days) with VCD (30 microM), 1,2-VCM (125-1000 microM), or vehicle. Twenty-eight days female CY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…Such cells may be located in the interstitium, and supports a capacity for the interstitial ovarian compartment to express high levels of xenobiotic detoxification enzymes. This suggests a potential role of the interstitium to provide protection of the germ cell population (ovarian follicles) against xenobiotic exposure (Cannady et al, 2003, Rajapaska et al, 2007a.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such cells may be located in the interstitium, and supports a capacity for the interstitial ovarian compartment to express high levels of xenobiotic detoxification enzymes. This suggests a potential role of the interstitium to provide protection of the germ cell population (ovarian follicles) against xenobiotic exposure (Cannady et al, 2003, Rajapaska et al, 2007a.…”
Section: Discussionmentioning
confidence: 99%
“…VCH is metabolized in the liver by cytochrome P450 enzyme isoforms, CYP2A and CYP2B (Fontaine et al, 2001a,b). Conversely, in the ovary the cytochrome P450 enzyme isoform CYP2E1 is thought to convert precursors to the ovotoxic form, VCD (Cannady et al, 2003;Rajapaska et al, 2007a).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown VCD to be the ultimate ovotoxicant, targeting both primordial and primary follicles for depletion (Hu et al, 2001;Smith et al, 1990;Sobinoff et al, 2010). As demonstrated in vivo and in vitro via knockout studies, VCH/VCM is bioactivated into VCD exclusively by the cyp2e1 isoform in the ovary (Rajapaksa et al, 2007a). Rajapaksa et al (2007a) cultured neonatal ovaries from both cyp2e1 +/+ and cyp2e1 -/-neonatal mice in VCM and VCD containing media.…”
Section: Bioactivationmentioning
confidence: 98%
“…Cellular toxicity occurs when these adducts disrupt the normal structure and/or function of these macromolecules, resulting in apoptosis, necrosis or carcinogenesis. The main site of xenobiotic biotransformation within the body is the liver, although the ovary is capable of both phase I and phase II metabolism (Igawa et al, 2009;Rajapaksa et al, 2007aRajapaksa et al, , 2007bShimada et al, 2003). Therefore, there is potential for the vulnerable primordial follicle to come into contact with bioactivated ovotoxic metabolites via several routes of exposure.…”
Section: Bioactivationmentioning
confidence: 99%
See 1 more Smart Citation